PENGARUH KARAKTERISTIK PEMERINTAH DAERAH DAN TEMUAN AUDIT BPK TERHADAP KINERJA PEMERINTAH DAERAH Studi pada Pemerintah Daerah Kabupaten/Kota di Provinsi Jawa Tengah Periode 2009-2011 - Renas Adi Nugroho; Dul Muid (Diponegoro Journal of Accounting, 2014)
Role of Government as public service and target development country become a better service. Therefore, this government have a control system, evaluation, and measurement performance achieved by local government. This study aims to analyze and examine to influence characteristics local government and audit findings BPK for performance Local Government District/Cities. Data were analyzed using Multiple linear regression analysis on 105 samples of local government report for year 2009, 2010, 2011, the study was able to prove that the wealth and status have positive significant effect on performance. Size, intergovernmental expenditure, capital expenditure and audit findings have negative significant affect the performance of the local government district/cities in the Central Java Province.